Successful trans-maternal nadolol pharmacotherapy in a fetus presenting with long QT syndrome type 2 complicated by torsade de pointes. Issue 6 (December 2020) - Shima, Yuriko; Horigome, Hitoshi; Nozaki, Yoshihiro; Lin, Lisheng; Ishiodori, Takumi; Yano, Yusuke; Takahashi, Miho; Murakami, Takashi; Yamasaki, Hiro; Takada, Hidetoshi
Abstract: Fetuses with congenital long QT syndrome (LQTS) may experience life-threatening arrhythmias, such as torsade de pointes (TdP), and/or functional atrioventricular block. However, trans-maternal pharmacotherapy for these cases is rarely reported and management practices have yet to be established. The fetus of a mother with genetically-confirmed LQTS type 2 (LQT2) presented with complex arrhythmias, diagnosed via magnetocardiography as ventricular arrhythmias (including TdP), at 28 weeks of gestation. After initiation of trans-maternal nadolol administration at 15 mg/d initial dosage and 30 mg/d subsequent dosage, the frequency of fetal ventricular arrhythmias decreased and almost disappeared within several days. The mother gave birth to the baby at full term without significant complications in either the mother or fetus. This is the first report that demonstrates the efficacy and safety of trans-maternal administration of nadolol for treatment of symptomatic LQT2 fetuses with TdP. <Learning objective: Prenatal diagnosis of congenital long QT syndrome (LQTS) is challenging, but characteristic arrhythmias, including sinus bradycardia, intermittent atrioventricular block and torsade de pointes (TdP), as well as family history of LQTS, can be clues to the diagnosis. If TdP is diagnosed in the fetus, trans-maternal administration of anti-arrhythmic drugs, such as beta-blockers, sodium channel blockers, and magnesium, could be effective to restore sinus rhythm and avoid intrauterine fetal death.>